The Long Duration Consequence of Using Anti-inflammatory and Immunosuppressive Drugs in the COVID-19 Epidemic - Imetkul, Ismailov; Hatem, Mortada Saleh; Mohammed, Sura Akram; Barrak, Rafah Sabah; Sabah, Ahmad; Rahim, Fakher (Trends in Immunotherapy, 2025)
The SARS-2 virus, responsible for the COVID-19 epidemic in early 2020, persists in posing a hazard to public health through the emergence of new mutations and surges in prevalence across several nations. Immunosuppressive medications treat both short-term and long-term inflammatory illnesses. The classification of these medications into various types is based on their action mechanisms. It is important to review the most recent data on the effectiveness and side effects of administering these drugs to patients because of the risk of severe inflammatory repercussions in COVID-19 patients, including acute respiratory failure and cytokine storm. This article presents accurate data on the advantages and disadvantages of using immunosuppressive medications in COVID-19 patients, while also providing a concise overview of the various types of these medications. Taken together, anti-inflammatory drugs and immune response inhibitors seem to be associated with better outcomes, such as shorter hospital stays and less need for mechanical ventilation, faster recovery from acute symptoms, and lower mortality rates, especially in the critically ill. However, one must consider the possibility of increasing treatment duration and vulnerability to fungal and bacterial infections. To minimize the negative effects of these medications, it is important to carefully balance their dosage and administration timing. Overall, the utilization of immunosuppressive medications, whether administered recently during illness or consistently for non-COVID-19 reasons, appears to have a beneficial impact on managing inflammation, expediting recovery, and decreasing mortality. However, it is crucial to exercise caution and avoid prescribing these drugs without proper consideration.